Reflective Kleisli subcategories of the category of Eilenberg-Moore algebras for factorization monads - Fiore, Marcelo; Menni, Matías (2005)
It is well known that for any monad, the associated Kleisli category is embedded in the category of Eilenberg-Moore algebras as the free ones. We discovered some interesting examples in which this embedding is reflective; that is, it has a left adjoint. To understand this phenomenon we introduce and study a class of monads arising from factorization systems, and thereby termed factorization monads. For them we show that under some simple conditions on the factorization system the free algebras are a full reflective subcategory of the algebras. We provide various examples of this situation of a combinatorial nature. -- Keywords: Combinatorial structures; Factorization systems; Joyal species; Kleisli categories; Monads; Power series; Schanuel topos.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 19/12/2008)
(2005) Theory and Applications of Categories, 15 (2), pp 40-65.
Keywords: TEORÍA DE CATEGORÍAS; MATEMÁTICA DE LA COMPUTACIÓN